PT-symmetry breaking in dual-core phosphate-glass photonic crystal fibers - Longobucco, Mattia (2024)
We investigate the properties of a soft glass dual-core photonic crystal fiber for application in multicore waveguiding with balanced gain and loss. Its base material is a phosphate glass in a P2O5-Al2O3-Yb2O3-BaO-ZnO-MgO-Na2O oxide system. The separated gain and loss cores are realized with two cores with ytterbium and copper doping of the base phosphate glass. The ytterbium-doped core supports a laser (gain) activity under excitation with a pump at 1000 nm wavelength, while the CuO-doped is responsible for strong attenuation at the same wavelength. We establish conditions for an exact balance between gain and loss and investigate pulse propagation by solving a system of coupled generalized nonlinear Schrödinger equations. We predict two states of light under excitation with hyperbolic secant pulses centered at 1000 nm: 1) linear oscillation of the pulse energy between gain and loss core (P T-symmetry state), with strong power attenuation; 2) retention of the pulse in the excited gain core (broken P T-symmetry), with very modest attenuation. The optimal pulse energy levels were identified to be 100 pJ (first state) and 430 pJ (second state).